Notes on Scarabaeinae fauna, their distribution and status in Nepal - Shrestha, Pusp Keshari (Journal of Natural History Museum, 2008)
Field inventory and compilation of previous reports on Scarabaeinae fauna of Nepal since the publication of F.W. Hope in 1831 has enumerated 89 species in 15 genera in this sub family. Distributional features of the previously reported and recently recorded dung beetles have also been presented in this paper. Gymnopleurus opacus Redt., Catharsius sagax Quens., Disphysema candezei Har., Liatongus rhadamistus (F.) Onthophagus discedens Sharp, O. penicillatus Har., O. triceratops Arrow, and O. bison Bouc. are new additions to the previous record in Nepal. J. Nat. Hist. Mus. Vol.22, 2005 p.99-120